Infrastructural nature : five-elements park - Roca, Estanislau; Smirnova, Aliaksandra; Harris, Sebastian Francis (Barcelona : Iniciativa Digital Politécnica. Oficina de Publicaciones Académicas Digitales de la UPC, 2019)
"Continuity and connectivity, transversality and linearity, permeability and porosity are the urban concepts that we took into account to understand and design within the Zhabei district in order to propose a project that suits the ideas of a well-networked, inclusive and sustainable city".
Texto en inglés y chino.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Rain and rainfall; Urban parks; Ferrocarriles -- Vías -- China -- Shanghai -- Proyectos -- Concursos; Parques urbanos -- China -- Shanghai -- Proyectos -- Concursos; China -- Shanghai; Libros electrónicos.